Spatial and temporal distribution of the currently-used and recently-banned pesticides in arable soils of the Czech Republic - Kosubová, P; Škulcová, L; Poláková, Š; Hofman, J; Bielská, L (Chemosphere, 2020)
This study presents monitoring data on the spatial and temporal occurrence of pesticide residues in arable soils of the Czech Republic and relates it to soil properties, pesticide usage and data on application provided by farmers. In total, 34 soils were sampled during 2014-2017, amounting to 136 samples which were analyzed for 60 pesticides and four transformation products. Conazole fungicides were frequently present in soils above the limit of quantification and/or above the 0.01 mg/kg threshold. Of the other pesticide types, the herbicides diflufenican, chlorotoluron, metolachlor, pendimethalin and terbuthylazine, fungicides azoxystrobin, carbendazim, fenpropidin, fenpropimorph and prochloraz and the insecticide methoxyfenozide were found in ≥20% of soils in at least one sampling campaign. Soils typically (>50%) contained 2-7 residues with a maximum of 14. For the 136 samples, 116 different mixtures were identified. The occurrence of pesticides was driven by their annual usage, their half-lives in soil, and their hydrophobicity. A comparison of the monitoring data and pesticide application data provided by farmers revealed that 63% of the applied pesticides are not likely to persist until the following growing season while up to 69% of pesticide residues found in soils could be inherited from the previous growing season(s).
Keywords: monitorování životního prostředí; triaziny; látky znečišťující půdu; Monitoring; Česká republika; Environmental Monitoring; Pesticides; Insecticides; Pesticide Residues; Transformation products; Czech Republic; aniliny; Triazines; Soil Pollutants; Conazole fungicides; herbicidy; rezidua pesticidů; průmyslové fungicidy; Soils; Soil; Aniline Compounds; Fungicides, Industrial; insekticidy; Triazine herbicides; Herbicides; pesticidy; půda